Short De-Etiolation Increases the Rooting of VC801 Avocado Rootstock - Duman, Zvi (Plants (Basel), 2020)
Dark-grown (etiolated) branches of many recalcitrant plant species root better than their green counterparts. Here it was hypothesized that changes in cell-wall properties and hormones occurring during etiolation contribute to rooting efficiency. Measurements of chlorophyll, carbohydrate and auxin contents, as well as tissue compression, histological analysis and gene-expression profiles were determined in etiolated and de-etiolated branches of the avocado rootstock VC801. Differences in chlorophyll content and tissue rigidity, and changes in xyloglucan and pectin in cambium and parenchyma cells were found. Interestingly, lignin and sugar contents were similar, suggesting that de-etiolated branches resemble the etiolated ones in this respect. Surprisingly, the branches that underwent short de-etiolation rooted better than the etiolated ones, and only a slight difference in IAA content between the two was observed. Gene-expression profiles revealed an increase in ethylene-responsive transcripts in the etiolated branches, which correlated with enrichment in xyloglucan hydrolases. In contrast, transcripts encoding pectin methylesterase and pectolyases were enriched in the de-etiolated branches. Taken together, it seems that the short de-etiolation period led to fine tuning of the conditions favoring adventitious root formation in terms of auxin–ethylene balance and cell-wall properties.